A desconstrução de discursos discriminatórios de sexualidade e gênero: apresentando diagnósticos e problematizações pertinentes à Educação - Carolli, André Luís [UNESP]; Cordeiro, Maria José De Jesus Alves (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (UNESP), Faculdade de Ciências, campus de Bauru., 2021)
Based on Derrida’s ideas on Deconstruction, there was the dismantling of discriminatory discourses of Sexuality and Gender - which are highly damaging socially - developed through interviews with students, especially influenced by the Archeology of Knowledge and the Genealogy of Power, according to Foucault. The objective was to ascertain the existence of flaws in scientific reasoning, inconsistencies and contradictions in discriminatory discourses. There is a strong presence of Logocentrism, on the basis of discrimination. In this context, the absence of Formal Logic, associated with the lack of scientific knowledge, leads 55.2% of students to uncritically adhere to propositions based on decontextualized biblical readings that exclude hermeneutics. Such erroneous readings feed discriminatory discursive formations, figuring as a permanent possibility of civilizing regression. Deconstruction presented itself as a viable path for the development of pedagogical strategies to combat prejudice, through education, at all levels and modes of teaching.

A partir das ideias da Desconstrução, de Derrida, desenvolveu-se a desmontagem de discursos discriminatórios da Sexualidade e Gênero, altamente danosos socialmente, a partir de entrevistas com educandos, especialmente, mediante a Arqueologia do Saber e a Genealogia do Poder, segundo Foucault. O objetivo foi apurar a existência de falhas de fundamentação científica, incoerências e contradições nos discursos discriminatórios. Apurou-se forte presença do Logocentrismo embasando discriminações. Nesse âmbito, a ausência da Lógica Formal, associada à falta de conhecimento científico, leva 55,2% de discentes a aderir acriticamente às proposições baseadas em leituras bíblicas descontextualizadas que excluem a hermenêutica. Tais leituras errôneas alimentam formações discursivas discriminatórias, figurando como permanente possibilidade de retrocessos civilizatórios. A Desconstrução se apresentou como caminho viável para o desenvolvimento de estratégias pedagógicas para combate a preconceitos, mediante a educação em todos os níveis e modalidades de ensino.
The deconstruction of discriminatory discourses of sexuality and gender: presenting diagnoses and problematizations that are relevant to Education
Keywords: Education and sexuality; Scientific knowledge; Formal logic; Discriminatory speech; Science and religion; Educação e sexualidade; Conhecimento científico; Lógica formal; Discurso discriminatório; Ciência e religião